Adaptation and validation of the Inventory of Family Protective Factors for the Portuguese culture - Cláudia Cristina Vieira Carvalho de Oliveira Ferreira Augusto; Beatriz Rodrigues Araújo; Vítor Manuel Costa Pereira Rodrigues; Maria do Céu Aguiar Barbieri de Figueiredo (Universidade de São Paulo, 2014)
OBJECTIVES: to adapt and validate the Inventory of Family Protective Factors (IFPF) for the Portuguese culture. This instrument assesses protective factors that contribute to family resilience. Studies addressing resilience are embedded within the salutogenic paradigm, i.e. it addresses protective factors of individuals or groups without underestimating risk factors or vulnerability.METHOD: in order to assess the IFPF's linguistic and conceptual equivalence, the instrument was translated, retro-translated and the think-aloud protocol was used. We then verified the instrument's sensitiveness, reliability and validity of results to assess its psychometric characteristics. A factor analysis was performed of the principal components with varimax rotation of the scale's items and Cronbach's alpha coefficient was calculated for each dimension. A total of 85 families with disabled children, selected through simple random sampling, self-administered the instrument.RESULTS: the IFPF presents psychometric characteristics that are appropriate for the Portuguese population (Cronbach's alpha = .90).CONCLUSION: the IFPF was adapted and validated for the Portuguese culture and is an instrument to be used in studies intended to assess protective factors of family resilience.